Biophysical characterization of lectin–glycan interactions for therapeutics, vaccines and targeted drug-delivery. (December 2014) - Christie, Michelle P; Toth, Istvan; Simerská, Pavla
Lectin–glycan interactions play a role in biological processes, host–pathogen interactions and in disease. A more detailed understanding of these interactions is not only useful for the elucidation of their biological function but can also be applied in immunology, drug development and delivery and diagnostics. We review some commonly used biophysical techniques for studying lectin–glycan interactions; namely: frontal affinity chromatography, glycan/lectin microarray, surface plasmon resonance, electrochemical impedance spectroscopy, isothermal titration calorimetry, fluorescent assays, enzyme linked lectin sorbent assay and saturation transfer difference nuclear magnetic resonance spectroscopy. Each method is evaluated on efficiency, cost and throughput. We also consider the advantages and limitations of each technique and provide examples of their application in biology, drug discovery and delivery, immunology, glycoprofiling and biosensing.